Absence of linkage between familial neural tube defects and PAX3 gene. Issue 3 (March 1995) - Chatkupt, S; Hol, F A; Shugart, Y Y; Geurds, M P; Stenroos, E S; Koenigsberger, M R; Hamel, B C; Johnson, W G; Mariman, E C
Abstract : Neural tube defects (NTD) are among the most common and disabling birth defects. The aetiology of NTD is unknown and their genetics are complex. The majority of NTD cases are sporadic, isolated, nonsyndromic, and generally considered to be multifactorial in origin. Recently, PAX3 (formerly HuP2, the human homologue of mouse Pax-3), on chromosome 2q35-37, was suggested as a candidate gene for NTD because mutations of Pax-3 cause the mouse mutant Splotch (Sp), an animal model for human NTD. Mutations in PAX3 were also identified in patients with Waardenburg syndrome type 1 (WS1). At least eight patients with both WS1 and NTD have been described suggesting pleiotropy or a contiguous gene syndrome. Seventeen US families and 14 Dutch families with more than one affected person with NTD were collected and 194 people (50 affected) from both data sets were genotyped using the PAX3 polymorphic marker. The data were analysed using affecteds only linkage analysis. The lod scores were -7.30 (US), -3.74 (Dutch), and -11.04 (combined) at theta = 0.0, under the assumption of the autosomal dominant model. For the recessive model, the lod scores were -3.30 (US), -1.46 (Dutch), and -4.76 (combined) at theta = 0.0. Linkage between PAX3 and familial NTD was excluded to 9.9 cM on either side of the gene for the dominant model and to 3.63 cM on either side of the gene for the recessive model in the families studied. No evidence of heterogeneity was detected using the HOMOG program. Our data indicate that PAX3 is not a major gene for NTD.